2013
DOI: 10.3389/fphys.2013.00197
|View full text |Cite
|
Sign up to set email alerts
|

Do physiological and pathological stresses produce different changes in heart rate variability?

Abstract: Although physiological (e.g., exercise) and pathological (e.g., infection) stress affecting the cardiovascular system have both been documented to be associated with a reduction in overall heart rate variability (HRV), it remains unclear if loss of HRV is ubiquitously similar across different domains of variability analysis or if distinct patterns of altered HRV exist depending on the stressor. Using Continuous Individualized Multiorgan Variability Analysis (CIMVA™) software, heart rate (HR) and four selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…However, to date there has been no consensus regarding the impact of the different components of physical fitness on HRV modulation during stress responses (Hautala et al, 2010; Bravi et al, 2013). We identified significant relationships between high HRV (absolute and change) and high aerobic fitness (MAS), and low % body fat.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date there has been no consensus regarding the impact of the different components of physical fitness on HRV modulation during stress responses (Hautala et al, 2010; Bravi et al, 2013). We identified significant relationships between high HRV (absolute and change) and high aerobic fitness (MAS), and low % body fat.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate variability (HRV) is a non-invasive approach to measure autonomic tone, 1 and variations in HRV have been associated with increased risk of pathologies and all-cause mortality. [1][2][3][4][5][6][7] The high-frequency power spectrum of HRV (HF-HRV) measures cardiac vagal tone, and studies have shown that decreases in parasympathetic vagal tone are associated with increased allostatic load and adverse health outcomes such as sepsis, necrotizing enterocolitis, chronic obstructive pulmonary disease, and peripheral artery disease, to name a few. 6,[8][9][10][11] Vagal output to the heart originates from brainstem neurons located in the nucleus ambiguous, 12 where neurons fire action potentials rhythmically, in a pattern similar to the respiratory rate.…”
Section: Introductionmentioning
confidence: 99%
“…8 In particular, the high frequency (HF) spectrum provides a reliable reflection of parasympathetic modulation, i.e., vagal tone, 9 which is associated with the maintenance of physiological homeostasis. Many studies have shown that HRV and vagal tone decrease in anxiety, stress, and inflammation/sepsis [10][11][12][13][14][15][16] ; indeed, the vagus also plays a critical role in the cholinergic anti-inflammatory reflex, 17,18 which has been shown to confer protection against tissue damage in many GI-related inflammatory diseases, including acute pancreatitis, colitis, and inflammatory bowel disease. [19][20][21] While HF-HRV provides a direct, non-invasive measure of vagal efferent activity 8 , additional potentially useful indirect measures of vagal activity on the cholinergic anti-inflammatory reflex include blood sampling for C-reactive protein and cytokine analysis.…”
Section: Introductionmentioning
confidence: 99%